2010
DOI: 10.1111/j.1600-0528.2010.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for caries prevention agents in adult patients: findings from the dental practice–based research network

Abstract: Objectives To identify factors that are significantly associated with dentists’ use of specific caries preventive agents in adult patients, and whether dentists who use one preventive agent are also more likely to use certain others. Methods Data were collected from 564 practitioners in The Dental Practice-Based Research Network, a multi-region consortium of participating practices and dental organizations. Results In-office topical fluoride was the method most frequently used. Regarding at-home preventive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 38 publications
2
44
3
2
Order By: Relevance
“…In fact, the dentist's overall subjective impression of the patient might have good caries-predictive power (Disney et al, 1992), but it is unclear how this information is incorporated into everyday practice. A recent survey of US practices suggests that a significant proportion of dentists had yet to adopt treatments based on assessment of caries risk (Riley et al, 2010), even when multiple expert-opinion tools are available for children [e.g., Caries Assessment Tool-CAT of the American Academy of Pediatric Dentistry, developed for use in multiple settings (2007); the American Dental Association's Caries Risk Tool (2008); the Caries Management by Risk Assessment tool (Ramos-Gomez et al, 2007)]. Therefore, a more objective, easy-to-implement, and validated risk tool is highly desirable, particularly for use in non-dental settings (e.g., schools, medical offices), to help target limited human/economic resources toward disease prevention.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the dentist's overall subjective impression of the patient might have good caries-predictive power (Disney et al, 1992), but it is unclear how this information is incorporated into everyday practice. A recent survey of US practices suggests that a significant proportion of dentists had yet to adopt treatments based on assessment of caries risk (Riley et al, 2010), even when multiple expert-opinion tools are available for children [e.g., Caries Assessment Tool-CAT of the American Academy of Pediatric Dentistry, developed for use in multiple settings (2007); the American Dental Association's Caries Risk Tool (2008); the Caries Management by Risk Assessment tool (Ramos-Gomez et al, 2007)]. Therefore, a more objective, easy-to-implement, and validated risk tool is highly desirable, particularly for use in non-dental settings (e.g., schools, medical offices), to help target limited human/economic resources toward disease prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The same questionnaire survey by the US DPBRN found that 69% of patients of 6-18 years of age received sealant application 13 , compared to 34% in the JDPBRN. Further, 77% of US DPBRN dentists provided sealants to more than 50% of their patients, compared to 32% in the JDPBRN 13 .…”
Section: Discussionmentioning
confidence: 95%
“…Further, 77% of US DPBRN dentists provided sealants to more than 50% of their patients, compared to 32% in the JDPBRN 13 . According to a previous Japanese survey of dental diseases and conditions in 2005, 27 the prevalence of dental sealant use on permanent teeth in Japanese aged 10 to 14 years was 26%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations